2016
DOI: 10.1016/j.tet.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

One-pot synthesis of pyrroles using a titanium-catalyzed multicomponent coupling procedure

Abstract: A simple one-pot procedure for the production of 2-carboxylpyrroles with 4-alkyl, 5-alkyl, 4aryl, 4-aryl-5-alkyl, or 3,4-diaryl substitution patterns is presented. The procedure involves the titanium-catalyzed multicomponent coupling of alkynes, primary amines and isonitriles to give 1,3-diimines in situ; the multicomponent product is then treated with the ethyl ester of glycine hydrochloride to give the NH-pyrrole. The reaction can be carried out with the neutralized glycine ester or with the hydrochloride sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Other oxygenated substrates such as 6d and 6e were poor cross coupling partners. Although nitro groups and esters are commonly tolerated in Suzuki reactions, 11 B NMR spectroscopic evidence indicates that deleterious chemistry with the 9-BBN group may be taking place (Fig. S150 †).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other oxygenated substrates such as 6d and 6e were poor cross coupling partners. Although nitro groups and esters are commonly tolerated in Suzuki reactions, 11 B NMR spectroscopic evidence indicates that deleterious chemistry with the 9-BBN group may be taking place (Fig. S150 †).…”
Section: Resultsmentioning
confidence: 99%
“…A series of pioneering studies has been reported by Odom on Ti-catalyzed multicomponent pyrrole synthesis based on hydroamination and iminoamination. [9][10][11] Following a slightly different strategy, we recently developed a multicomponent [2 + 2 + 1] Ti-catalyzed pyrrole forming reaction that yields the heterocycle in a single step. 12 Chemo-and regioselective intermolecular reactions can be achieved via the heterocoupling of trialkylsilyl-protected alkynes, which selectively engage in migratory insertion into a key azatitanacyclobutene [2 + 2] cycloadduct intermediate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aryl pyrroles bearing an ester functional group are commonly used in organic synthesis and medicinal chemistry as synthetic intermediates [2,3,4,5,6]. There are a great deal of methods for the preparation of aryl-substituted pyrroles with this pendant ester group, and generally, the pyrrole core is formed from functionalized precursors with complex structures employing various catalysts and ligands [7,8,9,10,11,12,13,14]. As our aim was to construct a small library of aryl-substituted pyrroles for biological activity assays, we found that it was inefficient to build these required pyrrole structures from some non-commercial starting materials.…”
Section: Introductionmentioning
confidence: 99%
“…There are other methodologies for the construction of pyrroles by using metal or base-catalyzed MCRs. Examples include gold [21], titanium [22], ruthenium [23], AgSbF 6 [24], silver [25], and n-BuLi [26] catalyzed reactions. Nonetheless, most of the synthetic approaches toward pyrrole synthesis suffer from disadvantages such as using either expensive toxic metal catalyst and base or harsh reaction conditions.…”
Section: Introductionmentioning
confidence: 99%